Limit Detection of Short Tandem Repeats (STR) Analysis on Touch DNA Samples - Saamia, Vira; Yudianto, Ahmad; Nurjayadi, Muktiningsih; Novitasari, Novitasari; Furqoni, Abdul Hadi (Universitas Gadjah Mada, 2024)
Forensic short tandem repeats (STR) profiling on touch DNA samples has emerged as a primary method for human identification. The stability and uniqueness of STR combination from the targeted locus in each individual make it a precision marker for human identification. Touch DNA samples can be found in traces of biological material shed from a person. This work aimed to identify the lowest concentration limit required for generating an interpretable DNA profile and the sensitivity of the STR loci applied. Touch DNA samples were collected from donors who were asked to hold a rope for 5 min. A double swab technique was used to lift the touch samples from the rope. These samples are subjected to DNA extraction and quantification. Two STR amplification cycles, 29 and 34 cycles, were used. DNA concentration greatly influences the success of amplifying the target allele at each STR locus to be interpreted into a complete DNA profile, shown by its allele peak. Touch DNA concentration >0.25 ng can produce a complete DNA profile. LCN method successfully amplified touch DNA with a concentration 0.0625–0.25 ng/µL. Limit detection of touch DNA analysis is 0.25 ng/µL. Low-copy DNA can still be analyzed within 0.0625–0.25 ng/µL.